Human Pituitary Growth Hormone Isolation and Properties of Two Biologically Active Fragments from Plasmin Digests - Li, Choh Hao (1974)
Two biologically active fragments have been isolated from plasmic digests of human pituitary growth hormone. It was shown that these two fragments were derived from the cleavage of the Arg-Thr (positions 134-135) and the Lys-Gln (positions 140-141) bonds of the hormone: one has 134 amino acids and the other 51 amino acids, respectively. The two fragments were active in the rat tibia and pigeon crop-sac tests, as well as in complement fixation experiments.